Improvements, trends, and new ideas in molecular docking: 2012–2013 in review. Issue 10 (21st March 2015) - Yuriev, Elizabeth; Holien, Jessica; Ramsland, Paul A.
<x xml:space="preserve">Abstract</x> Molecular docking is a computational method for predicting the placement of ligands in the binding sites of their receptor(s). In this review, we discuss the methodological developments that occurred in the docking field in 2012 and 2013, with a particular focus on the more difficult aspects of this computational discipline. The main challenges and therefore focal points for developments in docking, covered in this review, are receptor flexibility, solvation, scoring, and virtual screening. We specifically deal with such aspects of molecular docking and its applications as selection criteria for constructing receptor ensembles, target dependence of scoring functions, integration of higher‐level theory into scoring, implicit and explicit handling of solvation in the binding process, and comparison and evaluation of docking and scoring methods. Copyright © 2015 John Wiley & Sons, Ltd.